2016
DOI: 10.1016/j.jtcvs.2016.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Performance of allogeneic bioengineered replacement pulmonary valves in rapidly growing young lambs

Abstract: Biological valve conduits can enlarge via passive dilatation without matrix synthesis, but this would result in decreased cusp coaptational areas. Bioengineered valves demonstrated similar annulus enlargement as cryopreserved valves but usually retained larger areas of cuspal coaptation. Heat-shock protein 47-positive (collagen-synthesizing) cells were present in previously acellular bioengineered sinus walls and cusp bases, but rarely in more distal cusp matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Measures to ensure blinding of the investigators and other personnel is often poorly reported in animal studies [ 123 , 124 ]. We have identified only two studies [ 71 , 94 ] that reported blinding of the assessors on valve functionality. Blinding is especially important when it comes to qualitative outcome assessment, particularly if there is a subjective element in the outcome like echocardiographic evaluation of the valve or reading histological slides, both important in TEHV studies.…”
Section: Discussionmentioning
confidence: 99%
“…Measures to ensure blinding of the investigators and other personnel is often poorly reported in animal studies [ 123 , 124 ]. We have identified only two studies [ 71 , 94 ] that reported blinding of the assessors on valve functionality. Blinding is especially important when it comes to qualitative outcome assessment, particularly if there is a subjective element in the outcome like echocardiographic evaluation of the valve or reading histological slides, both important in TEHV studies.…”
Section: Discussionmentioning
confidence: 99%
“…This chemical treatment was accomplished by normalizing tissue pH, rehydrating the collagen helix moisture envelope, compacting collagen fibrils, and restoring soluble proteins by treating decellularized valves in a conditioning solution composed of citric acid, hyaluronic acid, lauryl alcohol, and species-specific protein. 12 , 23 , 97 , 98 Biomechanical evaluation revealed that the conditioning solution restored the stress relaxation behavior toward that of the native valve properties. 12 In an ovine allograft valve implant model, the conditioning process led to better hemodynamic performance, compared to cryopreserved and decellularized valves implanted without conditioning.…”
Section: Recellularization and Conditioningmentioning
confidence: 97%
“… 12 In an ovine allograft valve implant model, the conditioning process led to better hemodynamic performance, compared to cryopreserved and decellularized valves implanted without conditioning. 23 , 98 Improved re-endothelialization and matrix recellularization were observed following conditioning, although the interstitial subsurface repopulation was limited to the proximal portion of the leaflet. 23 , 98 Similar results were observed using a baboon model and conditioned human valves to simulate human paradigms.…”
Section: Recellularization and Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The report by Quinn and colleagues 1 provides a comparison of cryopreserved (CP) homograft pulmonary valves with pulmonary homograft valves that were bioengineered (BE) by decellularization and then conditioned with a unique solution of fatty alcohol containing human hyaluronin immediately before implantation in growing sheep. After 6 months, the authors found cellular ingrowth into both the BE and CP valved conduit grafts, but the extent of surface coverage of the BE valves was greater.…”
mentioning
confidence: 99%